Psychometric Validation of the Traditional Chinese Version of the Early Onset Scoliosis-24 Item Questionnaire (EOSQ-24). Issue 24 (15th December 2016) - Cheung, Jason Pui Yin; Cheung, Prudence Wing Hang; Wong, Carlos King Ho; Samartzis, Dino; Luk, Keith Dip-Kei; Lam, Cindy Lo Kuen; Cheung, Kenneth Man Chee
Abstract : Supplemental Digital Content is available in the text Abstract : Study Design: Questionnaire translation and validation. Objective: The aim of this study was to translate and cross-culturally adapt the Early Onset Scoliosis-24 item Questionnaire (EOSQ-24) into traditional Chinese, and to assess its validity, reliability, and sensitivity in Southern-Chinese patients diagnosed with early onset scoliosis (EOS). Summary of Background Data: Relying on radiographs alone for assessing treatment outcomes in EOS patients is inadequate. To properly gauge health-related quality of life, a disease-specific instrument that assesses patient quality of life and the burden of primary caregivers is necessary. The EOSQ-24 was created for this purpose, but it has not been adapted to the Chinese language. Methods: The translation and cross-cultural adaptation of the original English EOSQ-24 were performed using the method of double forward and single backward translations, followed by a panel review. EOS patients of Southern-Chinese descent were recruited, via convenience sampling from a scoliosis specialty clinic. These patients' parents/caretakers were then administered the traditional Chinese EOSQ-24, Likert Scale regarding the understanding of completed EOSQ-24, and the Child Health Questionnaire Parent Form 50 (CHQ-PF50) (Traditional Chinese). Reliability was analyzed using Cronbach alpha. Construct validity of domains and subdomains was assessed using Spearman correlation test against CHQ-PF50 domains with similar constructs. Sensitivity of the EOSQ-24 scores was determined by performing known group comparisons. Results: A total of 100 EOS patients were recruited. A very good reliability was demonstrated (Cronbach α: 0.896) and internal consistency of all domains was excellent (Cronbach α: 0.829–0.919). Subdomain scores of EOSQ-24 and CHQ-PF50 had significant correlations ( P < 0.001), indicating a good construct validity. Conclusion: This is the first psychometric study to translate and adapt the EOSQ-24 questionnaire for Chinese EOS patients and it has been found to have satisfactory validity, reliability, and sensitivity. It is a useful disease-specific instrument for assessing patients' quality of life and the burden of caregivers. Level of Evidence: 2